PENGARUH GREEN ACCOUNTING TERHADAP KINERJA BERKELANJUTAN (STUDI EMPIRIS PADA PERUSAHAAN ENERGI DI INDONESIA) - Luh Putu Puji Trisnawati; Yovita Ariani (JURNAL LENTERA AKUNTANSI, 2026)
This study investigates the impact of green accounting implementation on the sustainability performance of energy companies in Indonesia during the period 2020–2024. Using a quantitative approach and panel regression analysis, the study examines the influence of green accounting, environmental performance (measured by PROPER scores), and Material Flow Cost Accounting (MFCA) indicators specifically area coverage and production output on sustainability performance, with asset management as a mediating variable. The data was processed by e-views software and the findings reveal that green accounting and MFCA (particularly production output) significantly enhance sustainability outcomes, while environmental performance shows a weaker direct effect. Furthermore, asset management plays a crucial mediating role, particularly in amplifying the impact of production efficiency on sustainability. The results underscore the importance of integrating environmentally conscious accounting practices and efficient asset utilization to foster long-term sustainable development in the energy sector. These insights contribute to both theoretical frameworks and practical strategies for improving corporate sustainability performance in line with environmental governance standards.